ABOUT SOME APPROXIMATIONS TO THE CLOSED SET OF NOT TRIVIAL SOLUTIONS OF THE EQUATIONS OF GINZBURG - LANDAU - A. A. Fonarev (Научный вестник МГТУ ГА, 2016)
Possibility of use of a projective iterative method for search of approximations to the closed set of not trivial generalised solutions of a boundary value problem for Ginzburg - Landau's equations of the phenomenological theory of superconduction is investigated. The projective iterative method combines a projective method and iterative process. The generalised solutions of a boundary value problem for Ginzburg - Landau's equations are critical points of a functional of a superconductor free energy.